2012
DOI: 10.1002/imhj.21338
|View full text |Cite
|
Sign up to set email alerts
|

Expanding early childhood mental health consultation to new venues: Serving infants and young children in domestic violence and homeless shelters

Abstract: The number of infants and young children affected by homelessness and domestic violence is growing, and the effect of these experiences on children is wide-ranging. Early childhood mental health consultation (ECMHC) has expanded to these settings to help the adults attend to very young children whose needs are often obscured by families' crises. Recent research in ECMHC to childcare has cited the salience of the consultant-consultee relationship as the central contributor to positive change in caregiver's beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Indeed, housing likely reduces the stress among children inasmuch as it increases the sense of stability and safety. However, this study's findings suggest that intervening directly in the needs of these children can result in significant and powerful preventive effects, and has been recommended by others (Brinamen et al, 2012). …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, housing likely reduces the stress among children inasmuch as it increases the sense of stability and safety. However, this study's findings suggest that intervening directly in the needs of these children can result in significant and powerful preventive effects, and has been recommended by others (Brinamen et al, 2012). …”
Section: Discussionmentioning
confidence: 81%
“…Children of homeless mothers are not routinely offered services by shelter or treatment programs (Brinamen et al 2012; Weinreb et al, 2007), even though studies document increased stress and mental health problems among homeless children (Park et al, 2012). It may be that providers assume that when the mother's mental health and substance use problems are treated, or homelessness is resolved, problems observed among their children will remit (Brinamen et al, 2012). In fact, Cooke et al (2004) found that children of substance users showed reduced internalizing and externalizing behaviors following the treatment of their substance use disordered parent, even though the children were not directly treated.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the recommendation by Brinamen, Taranta, and Johnston () to expand early childhood mental health consultation (ECMHC) to homeless shelters is a promising approach to exploring how shelter environments can support infants and young children by promoting secure parent–child attachment. However, several mothers in our study were separated from their infant children, preferring to have kin care for their infants rather than bring them to shelter.…”
Section: Discussionmentioning
confidence: 99%
“…However, CAMHS is in a powerful position to not only champion the importance of the early identification of family violence, particularly in infancy [ 43 , 150 , 151 , 152 , 153 ], but to offer a therapeutic contribution to lives of the families they serve [ 151 , 154 , 155 , 156 , 157 , 158 , 159 , 160 ]. Furthermore, CAMHS has much to offer in how the prevalence and complexities of violence within families is thought about from a mental health perspective [ 49 , 161 , 162 , 163 , 164 , 165 ].…”
Section: Discussionmentioning
confidence: 99%